Into the deep blue yonder. - van Gelder, Tim (Quadrant Magazine)
Comments on the computer chess game between world champion Gary Kasparov and the International Business Machines (IBM) computer Deep Blue. Speculation on the amount of interest given to this game; Description of Deep Blue; Reference to interpretations of the Kasparov-Deep Blue game; Information on the movie `2001: A Space Odyssey'; Details on the computer's performance.